PERANCANGAN ALAT MONITORING SISTEM KERJA SOLAR PANEL BERBASIS IoT (INTERNET OF THINGS) - Kurnia Putra, Dian; Alfith, Alfith; Shaliha Rosa, Amila (Jurnal Teknologi dan Vokasi, 2023)
Creating a system that can track the position of sunlight to increase the efficiency of receiving light by solar panels, as well as monitor the power generated by solar panels based on the internet of things. The results of this study indicate that increasing solar panel power using a solar tracking system for static solar panels can optimize the output power of solar panels by 27.4%, while increasing solar panel power using a solar tracking system for solar tracking with a fresnel lens can optimize power. solar panel output by 14%.